Antara Sakral dan Profan: Analisis Dikotomi Durkheim dan Simbolisme Geertz dalam Ritual Hoyak Tabuik - Riska Ramadhani (Advances In Education Journal, 2025)
This study examines the sacred–profane relationship in the Tabuik tradition of Pariaman, which combines ritual mourning over the Karbala tragedy, popular festivity, intergroup rivalry, and tourism commercialization. Its aims are: (1) to analyze the construction of the sacred dimension through the separation of space and time, initial rituals, and Tabuik symbolism; (2) to explain the emergence of the profane dimension through Hoyak Tabuik, the rivalry between Tabuik Pasa and Tabuik Subarang, and economic–tourism integration; and (3) to examine the synthesis of sacred–profane tensions in the casting of the Tabuik into the sea. The study employs a descriptive qualitative approach with cultural ethnography through participant observation, in-depth interviews, and documentation studies, thematically analyzed using the theories of Durkheim, Geertz, Simmel, and Coser. The findings show that Tabuik is a socio-religious practice that dynamically negotiates the sacred–profane boundary while simultaneously renewing community social cohesion.